Growth response and nutritive value of Azolla and Alternanthera incorporated pelleted feeds on fingerlings of Cyprinus carpio var. communis: a preliminary study - Suresh, V R; Mandal, B K (Indian Journal of Fisheries, 2011)
A 40 day feeding experiment was conducted under laboratory conditions todetermine the suitability of dried aquatic fern Azolla and marshy weedAlternanthera philazeroides as ingredients in pelleted feed for a freshwater fishCyprinus carpio var. communis. A conventional diet (Fl) made of rice bran andmustard oil cake (1:1) was used as control against four diets (F2 to F5) incorporatedwith different levels of Azolla, Alternanthera, rice bran and mustard oil cake.Better weight gain, percentage growth and specific growth rate were obtained withFl (3.8Â±1.1 g, 52.78% and 0.81% respectively), followed by F2 (3.4Â±0.4 g, 50.75%and 0.77% respectively). Feed utilization and digestibility parameters were alsobetter with Fl, followed by F2. Although the conventional feed Fl produced highergrowth and low FCR, it appeared possible to incorporate dried Azolla andAlternanthera in supplementary feed for the fish